2018
DOI: 10.3390/jcm7120543
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association and Directionality between Mental Health Disorders and Substance Use among Adolescents and Young Adults in the U.S. and Canada—A Systematic Review and Meta-Analysis

Abstract: Background: The purpose of this systematic review was to examine the association and directionality between mental health disorders and substance use among adolescents and young adults in the U.S. and Canada. Methods: The following databases were used: Medline, PubMed, Embase, PsycINFO, and Cochrane Library. Meta-analysis used odds ratios as the pooled measure of effect. Results: A total of 3656 studies were screened and 36 were selected. Pooled results showed a positive association between depression and use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 68 publications
5
74
0
1
Order By: Relevance
“…This study found that the subjects with substance use were mainly males aged 20-39 years. This finding is similar to that of other researchers in this environment and internationally, who reported that youth especially males predominate in the substance use scene [2,5]. Most of the subjects in this study were found to have started taking substances before twenty years of age, with the youngest age of onset found to be 11years.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This study found that the subjects with substance use were mainly males aged 20-39 years. This finding is similar to that of other researchers in this environment and internationally, who reported that youth especially males predominate in the substance use scene [2,5]. Most of the subjects in this study were found to have started taking substances before twenty years of age, with the youngest age of onset found to be 11years.…”
Section: Resultssupporting
confidence: 91%
“…A number of studies conducted in the past decade in this environment have established that substance abuse and dependence (SAD) are relatively common [2,3]. Psychiatric comorbidity among substance users has been a topic of considerable interest and it has been widely recognized that anxiety and depression commonly co-exist with psychoactive substance abuse among adolescents and adults of both sexes [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, motivations for use differed among clusters: Risky Adolescents users (C1) and Risky young unemployed users (C2) mostly smoked for self-treatment (relaxation and sleep), and also more often received psychotropic treatment. Given the interplay between substance use and vulnerability to mental health disorders [33], identification of symptoms of anxiety or depression in those clusters may be an issue for the care of these individuals. Finally, risk-taking was also different: the first 3 groups drove more often after using cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…93,94 Notwithstanding these theoretical digressions and experimental evidence, the clinical impact of cannabis use on mood disorders is well-known and indirectly shows the relationship of these illnesses and the endocannabinoid system. For example, longitudinal studies have associated cannabis use during adolescence with later development of MDD, depressive symptoms, 95,96 and suicidal ideation. [97][98][99][100] In addition, a prospective study also suggested that adolescent cannabis use may be an independent risk factor for the development of hypomania in young adulthood.…”
Section: Current Evidencementioning
confidence: 99%